Kingdom ethics following Jesus in contemporary context - Stassen, Glen Harold, 1936-; Gushee, David P. 1962- (Downers Grove, IL IVP, 2003)
Includes bibliograhical references and index.
Keywords: Sermon on the mount -- criticism, interpretation, etc; Jesus Christ -- ethics